Palliative planning in an American shrinking city – Some thoughts and preliminary policy analysis. Issue 3 (27th May 2017) - Weaver, Russell
Abstract: Urban decline is a wicked problem that conventional tools of local government planning are not scoped to solve once and for all. Accordingly, local public policy and community development programs are increasingly aimed at mitigating symptoms rather than cause(s) of decline. These "palliative" efforts attempt to improve quality of life for existing residents in order to lower the probability of further decline. This research note describes a palliative policy from Buffalo, NY, and proposes a methodological strategy that uses Geographic Information Systems and difference-in-differences analysis to study its effects. Preliminary analysis suggests that the policy might be contributing to blight reduction in a targeted neighborhood. These pilot findings open the door for future empirical researchers to replicate the proposed methodology for longer time horizons in the study neighborhood, as well as to analyze palliative interventions in most any neighborhood where they are being deployed to treat symptoms of urban decline.